Analysis of the antibiotic consumption on the backdrop of the COVID-19 pandemic: hospital level - K. I. Karnoukh (Медицинский совет, 2021)
Introduction. According to available data, the frequency of prescribing antibacterial drugs to patients hospitalized with COVID-19 is many times higher than the level of bacterial infection recorded in them. This trend may make an extremely negative contribution to the problem of antibiotic resistance in the future, which makes it important to monitor and study the consumption of antibiotics in this category of patients.Aim of the study. To estimate the change in the consumption of antibacterial drugs in patients hospitalized with COVID-19 in a multidisciplinary hospital compared with the consumption in the pre-pandemic period, and to conduct a subsequent analysis of the detected changes.Materials and methods. This retrospective study, reviewed the medical records of patients hospitalized with COVID-19 in the Moscow city hospital No. 4 in the period from April 27 to December 31, 2020, as well as medical records of patients hospitalized in the same medical institution for the same period of 2019. Results of the use of antibacterial drugs were obtained. They were evaluated using the ATC/DDD methodology and then subjected to further analysis.Results. Total consumption increased from 31,576 DDD/100 bed-days to 220,609 DDD/100 bed-days among the patients hospitalized with COVID-19. The level of consumption of macrolides increased most significantly – from 0.024 DDD/100 bed-days to 147.898 DDD/100 bed-days. The level of consumption of penicillins increased from 2,346 DDD/100 bed-days to 15,892 DDD/100 beddays, cephalosporins – from 11.78 DDD/100 bed-days to 19,107 DDD/100 bed-days, fluoroquinolones – from 10,276 DDD/100 beddays to 25,535 DDD/100 bed-days.Conclusion. The consumption of antibiotics has increased dramatically on the backdrop of the COVID-19 pandemic. Based on the data of the frequency of bacterial complications in patients with COVID-19 (no more than 8%), a more rational approach to antibacterial therapy in this group of patients is needed to reduce the potential deterioration of the problem of antibiotic resistance.